Arabidopsis YEATS domain proteins facilitate DNA double-strand break repair via homology-directed pathways - Neeraja Vegesna; Laura Bouza-Morcillo; Clara Bourbousse; Yasaman Jami-Alahmadi; En Li; Maherun Nisa; Ana Marie S. Palanca; James A. Wohlschlegel; Julie A. Law (Proceedings of the National Academy of Sciences, 2026)
DNA double-strand break (DSB) repair is required to maintain genome integrity and organismal fitness. This process occurs within chromatin and although accurate repair requires extensive changes in chromatin structure and composition, chromatin effectors facilitating DSB repair remain largely unknown in plants. Using reverse genetics, we identified two chromatin readers, YAF9A and YAF9B, as new factors required for DSB repair in Arabidopsis . While only YAF9B is induced by DNA damage, both YAF9A and YAF9B are required for DSB repair, including via homology-directed repair pathways. Mechanistically, we found YAF9A and YAF9B denote distinct remodeling complexes: While YAF9A associates with both NuA4 and SWR1, YAF9B only associates with NuA4, defining a DNA-damage-specific version of this remodeling complex and linking NuA4 to DSB repair in plants. We also uncovered direct roles for YAF9A and YAF9B in DNA repair, rather than indirect roles in gene regulation, as yaf9 mutants showed normal transcriptional responses to DNA damage. Finally, we demonstrate that the YAF9B reader domain is required for DSB repair. These results link YAF9A, YAF9B, and their respective remodeling complexes, to DSB repair in a histone reader-dependent manner, expanding our understanding of how chromatin effectors regulate DSB repair in plants.